An Einstein encyclopedia - Calaprice, Alice; Kennefick, Daniel; Schulmann, Robert J.; Gale Group (Princeton Princeton University Press, 2015)
This encyclopedia contains entries on Albert Einstein's life and work. Entries on Einstein's scientific theories provide background and context, along with details about his assistants, collaborators, and rivals, as well as physics concepts related to his work. Coverage of Einstein's role in public life includes entries on his Jewish identity, humanitarian and civil rights involvements, political and educational philosophies, and religion.
part I. The personal and family spheres -- part II. A life in science -- part III. Identity and principles.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Einstein, Albert -- 1879-1955 -- Encyclopedias; Physicists -- Biography -- Encyclopedias; Relativity (Physics) -- History -- Encyclopedias; Physics -- History -- 20th century -- Encyclopedias